A STUDY ON TRENDING THE SEROPREVALENCE AND ANALYZING THE CHANGES IN SEROMARKERS OF DENGUE VIRUS INFECTION IN RECENT OUTBREAK BETWEEN APRIL TO SEPTEMBER,2024 FROM A TERTIARY CARE HOSPITAL IN BANGALORE - Dr Supriya Dey; Dr Girish N; Dr Priyanka Narayankar (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Introduction: Dengue virus is a single stranded positive sense RNA virus belonging to the genus flavivirus family Flaviviridae.[3] Dengue fever is a seasonal and emerging acute mosquito borne arbo-viral illness affecting tropical and sub-tropical countries. [4]This illness ranges from a mild asymptomatic form to severe dengue hemorrhagic fever (DHF) with or without dengue shock syndrome (DSS). [5] Objective : This study was conducted to know the seroprevalence trend and changes in seromarkers of Dengue virus in a tertiary care hospital, Bangalore, Karnataka, India. Materials and Methods: Over a period of six months from April 2024 to September2024, a total of 5250 blood samples from clinically suspected dengue patients were received in department of Microbiology laboratory. Serum was separated and subjected to enzyme immunoassay for detection of both Non Structural (NS1) antigen and IgM antibody. Results: During this study period, a total of 5500 blood samples were processed from suspected dengue cases. 250 hemolysed samples were excluded. Out of 5250 samples, 2750(52.38%) samples were found to be positive by different serological markers like NS1 Antigen (Ag), IgM antibody(Ab), or both NS1 Ag & IgM Ab. The overall seroprevalence rate was found to be 52.38%. Higher incidence was found in 9 to 17 years of age group and males were more affected than females. In this study period of six months, the month-wise seroprevalence rate was found to be 12% (153) in the month of April and May 2024 and was 26% (350) in the month of June and July 2024 and was 40% (522) in the month of August and September 2024. It clearly shows that there is an increase in the dengue cases.